Comparative analysis of cellular structures in fresh and dehydrated tropical fruits using confocal microscopy - Espeleta-Maya, A.; Martínez-Trinidad, J.; Moreno-Pacheco, L.; García-León, R. A. (Frontiers in Sustainable Food Systems, 2025)
This study quantitatively investigated dehydration-induced microstructural and biochemical transformations in Hass avocado, sugar mango, papaya, and Honey Gold pineapple using confocal laser scanning microscopy (CLSM). The methodology involved comparing fluorescence intensity in fresh and dehydrated tissues and validating these measurements through proximate composition and statistical analysis, including a three-way ANOVA (fruit species × temperature × air velocity). Results showed increased fluorescence in avocado (31%), mango (28%), and pineapple (35%), with strong correlations to protein enrichment (R² > 0.92), while papaya exhibited a 22% decrease despite higher protein content, suggesting conformational rearrangements that reduced fluorophore accessibility. The ANOVA confirmed that fruit species significantly affected fluorescence intensity and protein content (p < 0.0001), temperature had a moderate effect (p = 0.0112), and air velocity showed no significant influence (p = 0.13). Overall, CLSM proved to be a reliable tool for linking dehydration severity with molecular and nutritional transformations, offering a robust framework for optimizing drying parameters and enhancing the quality preservation of tropical fruits.